Предпосылки, принципы и подходы к моделированию механизма реализации комплекса инструментов экологического менеджмента промышленного предприятия - Святохо, Н.В. (Культура народов Причерноморья, 2014)
Статья посвящена актуальной проблеме моделирования механизма реализации комплекса
инструментов экологического менеджмента промышленного предприятия. Уточнено понятие
механизма для задачи моделирования механизма реализации комплекса инструментов экологического
менеджмента промышленного предприятия. Определены принципы, этапы моделирования на основе
использования процессного подхода и факторы, влияющие на особенности моделирования механизма
реализации комплекса инструментов экологического менеджмента промышленного предприятия. Стаття присвячена актуальній проблемі моделювання механізму реалізації комплексу
інструментів екологічного менеджменту промислового підприємства. Уточнено поняття механізму
для завдання моделювання механізму реалізації комплексу інструментів екологічного менеджменту
промислового підприємства. Визначено принципи, етапи моделювання на основі використання
процесного підходу та фактори, що впливають на особливості моделювання механізму реалізації
комплексу інструментів екологічного менеджменту промислового підприємства. The article is sanctified to the issue of the day of design of mechanism of realization of complex of
instruments of ecological management of industrial enterprise. The necessity of realization of complex of
instruments of ecological management of enterprise as bases of his ecological informative system is reasonable.
The concept of mechanism is specified for the task of modeling of mechanism of realization of complex of
instruments of ecological management of industrial enterprise. Principles are set forth and the modeling stages
are distinguished on the basis of the use of process approach. The aim of such modeling is presentation of
sequence and maintenance of the stages of process of realization of complex of instruments of ecological
management of industrial enterprise, amount, correlation of necessary for this purpose resources, present
limitations, managing influences etc., that will allow to inculcate such process in practical activity of industrial
enterprise with maximal efficiency. Factors influencing on the features of modeling of mechanism of realization
of complex of instruments of ecological management of industrial enterprise are certain. Expediency of the use
of standard of IDEF0 is reasonable for the modeling of process of realization of complex of instruments of
ecological management of industrial enterprise.